[Student choir singing on stage] (1995)
A group of mostly Black students (there appears to be one White student), with ribbons pinned to their shirts, are singing into a microphone on the University Union plaza stage. Two other Black people are standing in the foreground below the stage level, and the person on the left is wearing a ribbon.